2020
DOI: 10.1007/s13592-019-00709-5
|View full text |Cite
|
Sign up to set email alerts
|

CYP6AS8, a cytochrome P450, is associated with the 10-HDA biosynthesis in honey bee (Apis mellifera) workers

Abstract: Mandibular gland (MG) secretions of honey bee are synthesized through a three-step bifurcation pathway, and the initiate hydroxylation step is carried out by cytochrome P450 enzymes (P450). We have previously revealed that CYP6AS8 and CYP6AS11 are possibly participating in this process. In this study, we evaluated the function of CYP6AS8 in honey bee worker's MG using RNA interference technology, and we investigated the expression pattern of CYP6AS8 in MGs from workers of different ages. We found that the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, P450 enzymes have been implicated in the synthesis of pheromones within the mandibular glands of honey bees [24]. CYP6AS8 plays a crucial role in the synthesis of mandibular acids in honey bee workers and is likely responsible for the hydroxylation of steric acid [47]. The downregulation of CYP6AS8 leads to a significant decrease in the content of 10-HDA, indicating that CYP6AS8 is essential for the biosynthesis of 10-HDA [47].…”
Section: Oa Induces 10-hda Biosynthesis In Worker Bee Mg In a Concent...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, P450 enzymes have been implicated in the synthesis of pheromones within the mandibular glands of honey bees [24]. CYP6AS8 plays a crucial role in the synthesis of mandibular acids in honey bee workers and is likely responsible for the hydroxylation of steric acid [47]. The downregulation of CYP6AS8 leads to a significant decrease in the content of 10-HDA, indicating that CYP6AS8 is essential for the biosynthesis of 10-HDA [47].…”
Section: Oa Induces 10-hda Biosynthesis In Worker Bee Mg In a Concent...mentioning
confidence: 99%
“…CYP6AS8 plays a crucial role in the synthesis of mandibular acids in honey bee workers and is likely responsible for the hydroxylation of steric acid [47]. The downregulation of CYP6AS8 leads to a significant decrease in the content of 10-HDA, indicating that CYP6AS8 is essential for the biosynthesis of 10-HDA [47]. The vital role of CYP6AS8 in the hydroxylation processes involved in 10-HDA biosynthesis in worker bees has been extensively documented by Fujita et al [48] and Wu et al [24].…”
Section: Oa Induces 10-hda Biosynthesis In Worker Bee Mg In a Concent...mentioning
confidence: 99%
“…In nature, worker bees synthesize 10-HDA in their mandibular glands, with a single worker bee synthesizing up to 60 μg of total 10-HDA. In the mandibular gland of worker bees, acetic acid undergoes an acetylation reaction in the fatty acid synthesis pathway, which is then hydroxylated at the ω-position to form stearic acid in a catalytic process involving cytochrome P450 (CYP), which then undergoes a desaturation reaction via β-oxidation to form 10-HDA . Additionally, 3-ketoacyl coenzyme A thiolase and recombinant electron-transfer flavoprotein β polypeptide also play important roles in 10-HDA synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…In the mandibular gland of worker bees, acetic acid undergoes an acetylation reaction in the fatty acid synthesis pathway, which is then hydroxylated at the ωposition to form stearic acid in a catalytic process involving cytochrome P450 (CYP), which then undergoes a desaturation reaction via β-oxidation to form 10-HDA. 11 Additionally, 3ketoacyl coenzyme A thiolase and recombinant electrontransfer flavoprotein β polypeptide also play important roles in 10-HDA synthesis. 12 Currently, the specific enzyme system and molecular mechanism of 10-HDA synthesis in worker bees remain unclear, posing challenges to regulating the natural synthesis of 10-HDA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that, as a result of different pollen feeding, 10-HDA contents can vary while still meeting the requirement of the international standard of RJ [ 9 , 10 ]. Interestingly, studies with deuterated substrates have revealed that the hydroxylation of FAs at the ω-position is likely catalyzed by P450 enzymes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%